Detection of Carbapenem-Resistant Klebsiella pneumonia using two Sensitivity Methods - Ghusoon Ali Abdulhasan; Suzan Yousif Jasim; Hula Younis Fadhil (College of Pharmacy / Mustansiriyah University, 2015)
Carbapenems, potent β-lactams antibiotics, were initially used as last-resort treatments for severe Gram-negative bacteria such as Klebsiella pneumonia. These bacteria were considered one of Enterbacteriaceae family associated with pneumonia and urinary tract infection. In the current research, Carbapenems were studied to identify the resistant K. pneumonia isolates and identifying the relation with some β-lactam resistance to avoid their abuse for treatment.             A urine sample got from 80 infected female with chronic urinary tract infection, these samples tested for K. pneumonia and their carbapenemase production. The procedure was based on disc diffusion and Landman e,t al. methods. The results pointed out that Klebsiella pneumonia is significantly present in patients with urinary tract infection, the carbapenem resistance in disc diffusion and Landman procedure was 100% and 88.5% for meropenem (MEM), while it was 57.2% and 65.4% for imipenem (IPE), respectively. Regarding the carbapenem resistance in same isolate for both (MEM and IPE), 69.23% (18/26) were coincidence and 30.77% (8/26) were mismatch in both methods. In addition, the Landman procedure more accurate than disc diffusion for carbapenem resistance and there is a strong association with Beta-lactam resistance.  It can be conclude that there is a high incidence of carbapenem resistance in local isolates of Klebsiella pneumonia. We recommend to use the supercarba media in diagnoses of bacteria routine work because it is more specific along with disc diffusion method for patients with urinary tract infection and the use of other treatments to decrease the level of resistance.